The quintuple helix innovation model: a pathway to sustainable development in marginalized rural communities - Auradian Marta; Rury Febrina; Wan Asrida; Raja Muhammad Amin; Zulfa Harirah. MS (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This research is based on the empirical fact that there is an increase in the status of villages from the majority of Underdeveloped and Very Underdeveloped Villages in 2022 to Developed Villages in 2023. This research focuses on discussing the development of very underdeveloped villages in Kampar Regency in the perspective of the quintuple helix, with the characteristics of wetland areas and conservation areas that have their own challenges in village development. This research is included in the qualitative approach with the type of phenomenology. The results of this study are based on the quintuple helix model which shows the cooperation of 5 (five) important actors, namely the state (government), private sector, academics, media, and the community as well as support from the natural environment in the village. Quintuple Helix, in this study, visualizes collective interaction and knowledge exchange through five subsystems (helix): (1) the education system, (2) the economic system, (3) the natural environment, (4) the media and culture-based society (as well as civil society), (5) and the political system. It can be concluded that the quintuple helix framework in this study has involved many of the previously mentioned actors but has not provided a significant impact on village development, especially villages that were previously very underdeveloped in Kampar Kiri Hulu District, Kampar Regency.